Estudio de factibilidad para la creación de una empresa en la ciudad de Cali, dedicada a la comercialización y exportación de artesanías colombianas (Bolsos, billeteras, correas y línea hogar) elaboradas a base de fique (2011)
Feactibility study for the creation of a company in Cali city, dedicated to the marketing and Colombia crafts export specialy, bags, wallets, belts and home line developed on fiq base, born by own initiative of two students of the Quindío university and according to knowledge, investigations, consultants and all the support that was through marketing company of craft products to contribute to the development of traditional sector with the bussiness creation and export; is necessary to mention that for the correct operation, we had in mind the technical study and the infrastructure that allow and facilitate the marketing process and the activities that the company needs to performing the provision of services; in order to promote our cultural legacy in other countries. in addition, surveys were conducted in different parts of Cali city, this allowed to take a look deeper into the subject and the staticts showed a favorable outcome that allow to know more broadly tastes and consumer preferences for when buying a product made from 100% natural materials of excellent quality and innovation. For the development study were considered very important factors national and international, mainly from the city of Cali and the country of France-Marsella, sector study, factors economic, political, social, cultural, marketing, distribution channels, the purpose of determining the power supply, demand, trade policy, capacity purchasing power and taste of potential customers. Study to financial notes to the company will have sustainable financial projections, as it is estimated that each year will increase sales by 25% allowing the first year of the company activities payback obtaining a minimum income.